The culture of flat earth and its consequences. Issue 2 (1st October 2020) - Erlaine, Dónal Mac
Tracing some elements of the history of science, such as the tradition of map-making beginning in ancient times, this article aims to link together some factors that have led to the contemporary phenomenon of flat earth belief. Springing from a political fringe culture steeped in a 'will-to-mistrust', flat earth belief has gained huge popularity in recent years. The total rejection of science in favour of opinion is today a feature of the discursive landscape, and nowhere it is more poignant than in flat earth belief. Furthermore, it leaks from a mistrust of science to mistrust of culture itself. Ultimately it falls to the agency of recent communication technologies, that is, the internet, where this culture is able to gain traction in popular discourse. Through a very simple geometrical argument needing no equipment, I demonstrate that the earth must be spherical (or near-so), and this ultimately points to the technocratic culture today that has paradoxically led to this unpredicted phenomenon. Moreover it is a dangerous trend, and this piece aims to highlight why this is so.